A prospective study of association of inflammatory markers with BMI in women with polycystic ovarian syndrome - Jain, Shalin; Barya, Smita; Sharma, Rajrani; Joshi, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Many studies have demonstrated the association between polycystic ovary syndrome (PCOS) and chronic low-grade inflammation to be of unknown mechanism or an unclear cause; which could either be due to the underlying obesity, insulin resistance, or the polycystic ovary syndrome itself. The aim of our study was to find if there was any correlation between the inflammatory markers and body mass index (BMI) in women with PCOS. Methods: Our study included 100 women aged between 18-45 years with PCOS and were recruited for the study in the obstetrics and gynecology department, Pacific Medical College and Hospital, Rajasthan from October 2020 to April 2022. The enrolled patients then underwent a series of clinical, ultrasonographic and biochemical investigations. Results: WBC was positively correlated with BMI (r=0.453, p<0.000) Along with that, we were also able to establish a moderate degree positive correlation between BMI and serum CRP levels (r=0.396, p<0.000). A high degree significant positive correlation was found between ESR count and BMI (r=0.537, p<0.000) and platelet count and BMI (r=0.386, p<0.000). Conclusions: We discovered that higher WBC concentration, ESR count, platelet count, and serum CRP levels are linked to PCOS. Increase in serum inflammatory cardiovascular risk markers are brought on by PCOS and obesity. In order to determine the relative contributions of various factors, such as insulin resistance, androgen status, and BMI, further studies need to be carried out with a larger sample size as the mechanism for the chronic low-grade inflammation still remains unclear.